Transformational Learning Through Shifting Global Perspectives: The Impact of COVID-19 on a Global Classroom in the U.S. and Liberia - Devereux, Taryn; Glenn, Anna (Journal of International Students, 2022)
The Global Classroom Model (GCM) is a project-based, cross-cultural, and virtual course conducted in partnership between institutions of higher education. Instructors at the University of Maryland (UMD) and the Liberia International Christian College (LICC) co-developed and co-instructed a novel and innovative Global Agriculture iteration of the Global Classroom (GC) course and collected data from students (n= 46) and stakeholders (n=18) through 2019, 2020, and 2021. This research used mixed-method pre/post interviews to address changes in attitudes, aspirations, and perceptions, and to better understand student experiences in global education. Students reported an increase in technical skills, “global perspective,” and feelings of “empowerment” through being able to work internationally on community-driven activities. This longitudinal study illuminates the impact of COVID-19 on a unique global learning experience, and highlights the broader opportunities and challenges found in designing truly collaborative global learning while also providing insights for practical implementation.